Isolation of Artediffusin (Tehranolide) as a New Antimalarial Agent - Rustaiyan, Abdolhossein; Nahrevanian, Hossein; Kazemi, Masoud (Asian Journal of Chemistry, 2011)
A few alternative drugs are under development, necessitating urgent efforts to identify new classes of antimalarial agents. There is a need to find new, effective and affordable remedies for malaria, including those derived from plants. The clinical utility of the Chinese discovery of artemisinin from the herb Artemisia annua has stimulated much interest in traditional plants as potential sources of new antimalarial drugs. The emergence of drug-resistant strains of Plasmodium falciparum has resulted in an urgent need to develop new antimalarial chemotherapeutic agents. The rich plant diversity and long history of traditional medicine in Iran warrants investigation and may be a valuable source of novel compounds. In this study, the antimalarial activity of artediffusin (tehranolide), a sesquiterpene lactone with an endoperoxide group, on plasmodium berghei in vivo on the mice model of malaria was investigated. It demonstrates that artediffusin which has been isolated from Artemisia diffusa inhibit the growth of plasmodium berghei in vivo in NMRI mice.